Some thoughts about the evolution of human behavior : a literature survey - Boucot, A. J. 1924- (Archaeopress Archaeology, 2021)
On his death, Arthur Boucot (1924-2017) left an unfinished manuscript in which he surveyed the skeletal, behavioural, and cultural changes that have characterized Homo from its first recognition in the Late Pliocene to the present. The results, edited after his death, provide a heavily referenced sourcebook for future workers in diverse fields.